Predictors of Counterproductive Work Behavior among Nurses: A Case Study of South Punjab (Medical Forum Monthly, 2022)
Objective: To investigate the role of burnout in predicting nurses’ counterproductive work behavior and to explore the buffering role of forgiveness and emotional intelligence between burnout dimensions and counterproductive work behavior.Study Design: Cross sectional studyPlace and Duration of Study: This study was conducted at the 6 different public and private hospitals of Multan, Pakistan from January 2020 to March 2020.Materials and Methods: A total 200 nurses (both sexes) with age ranges from 18-44 years participated in the study. After taking informed consent, demographic sheet along with four sets of instruments; Maslach Burnout Inventory (MBI), Counterproductive Work Behavior checklist (CWB-C), Forgiveness scale and Brief Emotional Intelligence scale (BEIS) were distributed among participants for collection of data. Data was analyzed using SPSS-23.Results: Findings revealed that all dimensions of burnout significantly positively predicted CWB among nurses. No evidence was found regarding the indirect effect of burnout dimensions on CWB through forgiveness. Furthermore, emotional intelligence moderated the positive relationship between two burnout dimensions (emotional exhaustion and personal accomplishment) and CWB but not moderated the depersonalization and CWB relationship.Conclusion: Findings suggests that emotional intelligence is a personal resource that organizations may foster in nurses to minimize emotional exhaustion and lack of personal accomplishment and its subsequent negative effect on CWB.